Pengaruh Penggunaan Tipe Card Sort Pada Pembelajaran PPKN Terhadap Hasil Belajar Peserta Didik Kelas IV SD Negeri 3 Sukamulya - Hikmah Salsyabila Aulia; Dinie Anggraeni Dewi; Agus Mulyana (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This research is motivated by the learning process which is still monotonous or only uses the lecture method and the lack of variations in learning so that students become less active in the learning process. The learning method used is quantitative with a one group pretest-posttest design which in its implementation only involves one class as an experimental class without any comparison class (control class). The purpose of this study was to determine the effect of using card sort types in learning Pancasila Education on student learning outcomes in class IV SD. Hypothesis testing was carried out with the Wilcoxon non-parametric test. Based on the results of the paired sample difference test using the Wilcoxon test with the help of SPSS, a p value of 0.000 (p <0.05) was obtained, which means that Ho is rejected and Ha is accepted, which means that there is a significant difference in the average pretest and posttest scores for students. or interpreted that the treatment of students is proven to be able to increase student scores.